One-Pot Synthesis of Triarylpyridines in Ionic Liquid and Their Catalyzed Active on a Simple Diels-Alder Reaction - Wu, Hui; Wan, Yu; Ye, Ling; Lu, Leilei (Asian Journal of Chemistry, 2010)
2,4,6-Triarylpyridines were synthesized by the cascade reaction of aromatic aldehyde, acetophenone and NH4OAc (1:2:5) in the presence of HOAc in ionic liquid [BmIm][BF4]. The method related to environmental friendly, simplicity, very effective and lower costs, is suitable for the synthesis of arrays of compounds. Their catalyzed activity on a simple Diels-Alder reaction was also studied.